Separation of Th from leachate of monazite sulphation process using amine solvent extraction - Luu, Xuan Dinh; Nguyen, Thanh Thuy; Le, Ba Thuan; Le Thi, Mai Huong (Nuclear Science and Technology, 2018)
The solvent extraction is one of the most common method for separating Th from solution. Primary amine has higher selectivity for the extraction of Th(IV) than U(VI) and RE(III) in sulfate media. N1923 (a primary aliphatic amine with amino nitrogen linked to a secondary carbon consisting of branched alkyl groups in C19–23 range) is commonly used to extractTh. At room temperature using 0.1M N1923 amine as solvent in this work, the results showed thatthorium maximum extraction capacity was about 2.5g/L with concentration of sulfuric acid in the aqueous phase was 1M and for 3 minutes shaking. At room temperature for 3 minutes shaking the best conditions for scrubbing process was using the mixture of acids H2SO4 0.2M and HNO3 0.1M, result inover 75%, Th was scrubbed in the aqueous phase only 0.7%. The separation of Th from leachate of monazite sulphation process was carried out on a multistage continuous flow extraction device (12 boxes), the thorium purity was 98%. Therefore, the use of amine solvents can purify thorium from rare-earth solutions in a sulfate medium